Archaea: A Gold Mine for Topoisomerase Diversity - Garnier, Florence; Couturier, Mohea; Débat, Hélène; Nadal, Marc (Frontiers in Microbiology, 2021)
The control of DNA topology is a prerequisite for all the DNA transactions such as DNA replication, repair, recombination, and transcription. This global control is carried out by essential enzymes, named DNA-topoisomerases, that are mandatory for the genome stability. Since many decades, the Archaea provide a significant panel of new types of topoisomerases such as the reverse gyrase, the type IIB or the type IC. These more or less recent discoveries largely contributed to change the understanding of the role of the DNA topoisomerases in all the living world. Despite their very different life styles, Archaea share a quasi-homogeneous set of DNA-topoisomerases, except thermophilic organisms that possess at least one reverse gyrase that is considered a marker of the thermophily. Here, we discuss the effect of the life style of Archaea on DNA structure and topology and then we review the content of these essential enzymes within all the archaeal diversity based on complete sequenced genomes available. Finally, we discuss their roles, in particular in the processes involved in both the archaeal adaptation and the preservation of the genome stability.